Efforts to Improve Mathematics Learning Outcomes Using the Problem Based Learning Model in Grade III Students of SDN 067240 Medan - Harahap, Putri Nadiah; Wahyuni, Sri; Harahap, Lenny Sari (Jurnal Riset Ilmu Pendidikan, 2025)
This study aims to improve mathematics learning activities in class III of SDN 067240 Medan Tembung by implementing the Problem Based Learning learning model. The type of research used is Classroom Action Research (CAR). This study was conducted in two cycles. With the research subjects of class III B students of SDN 067240 Medan Tembung totaling 6 male students and 6 female students. The instrument used in this study was a test. The data analysis technique used was quantitative descriptive. The results of the study showed that there was an increase in mathematics learning outcomes by implementing the Problem Based Learning model. The increase in student learning outcomes can be seen from the results of data acquisition from cycle I to cycle II. In cycle I, there were 7 students who completed the class 58.3% while there were 5 students with class 41.6% who had not completed mathematics learning. Then in cycle II, there was an increase of 10 students who completed the class 83.3% and there were 2 students who had not completed the class 13.3%. Because classically it has reached 83.3% of students who have completed it, this study is said to be successful.